Community Development Employment Projects : participant information booklet. - Australia. Aboriginal and Torres Strait Islander Commission ([Canberra?] : ASTIC, 1995)
Outlines operation of the CDEP for those people on or thinking of joining it; sets out rights, responsibilities, rules.
"Aboriginal Employment Development Policy"
"January 1995"
Keywords: Community Development Employment Projects (Australia); Aboriginal Australians -- Employment -- Government policy; Employment - Programs - Community Development Employment Projects (CDEP); Employment - Programs; Employment - Unemployment; Australia